The Effectiveness of Group Counselling with Self-Talk Technique to Improve Students’ Career Aspiration and Self-Efficacy - Ari, Umi; Sugiharto, Dwi Yuwono Puji; Awalya, Awalya (Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to know the effectiveness of group counseling with self-talk technique to improve students’ career aspiration and efficacy. This experimental study used pre-test – post-test group design by involving 14 students of Al Falah Vocational High School Winong Pati (SMK Al Falah Winong Pati) as the members of the group. Moreover, the research was done by testing repeated measures MANOVA showed that group counseling with self-talk technique was effective to improve students’ career aspiration and efficacy. At last, the discussion of the findings of this study is directed to assert the effectiveness of group counseling with self-talk technique to improve students’ career aspiration and efficacy.